Efeitos das condições climáticas no trimestre de nascimento sobre asma e pneumonia na infância e na vida adulta em uma coorte no Sul do Brasil The effects of season at time of birth on asthma and pneumonia in childhood and adulthood in a birth cohort in southern Brazil - David Alejandro González; Cesar G. Victora; Helen Gonçalves (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
Avaliaram-se os efeitos do clima no trimestre do nascimento e nos seis primeiros meses de vida (temperatura média em tercis) sobre as hospitalizações por asma e pneumonia em pré-escolares e sobre o diagnóstico de asma em adultos pertencentes ao estudo de coorte de nascimento de 1982 de Pelotas, Rio Grande do Sul, Brasil. Essa coorte incluiu todos os 5.914 nascidos vivos naquele ano, dos quais, 77% foram acompanhados até a idade adulta (23-24 anos). Os resultados demonstraram que os nascidos entre abril e junho (outono) apresentaram risco de hospitalização por pneumonia e asma/"bronquite" 1,31 (IC95%: 0,99-1,73) a 2,35 (IC95%: 1,11-4,99) vezes maior do que os nascidos entre janeiro-março (verão). O risco de hospitalizações conforme a temperatura média nos seis primeiros meses de vida foi 1,64 (IC95%: 1,26-2,13) a 3,16 (IC95%: 1,63-6,12) vezes maior no tercil frio do que no quente. Os efeitos da sazonalidade diminuíram com a idade, sendo pouco evidente a associação com asma aos 23-24 anos. As hospitalizações foram mais freqüentes entre crianças pobres, mas os efeitos da sazonalidade sobre a pneumonia foram mais evidentes entre os ricos. This study evaluated the effects of seasonal weather at time of birth and ambient temperature during the first six months of life on hospitalizations due to asthma and pneumonia in preschool children and on diagnosis of asthma in adulthood among individuals from the 1982 birth cohort in Pelotas, Rio Grande do Sul, Brazil. The cohort included 5,914 live births, of which 77% were followed up until adulthood (23-24 yr). The risk of hospitalization due to pneumonia and asthma among children born from April to June (autumn) was 1.31 (95%CI: 0.99-1.73) to 2.4 (95%CI: 1.11-4.99) times higher than that of children born from January to March (summer). For temperature in the first six months of life, risk of hospitalization was 1.64 (95%CI: 1.26-2.13) to 3.16 (95%CI: 1.63-6.12) times higher for children born in the coldest as compared to the hottest temperature tertile. The effects of seasonality decreased with age, and the association with asthma in adulthood was weak. Hospitalizations in poor children were more frequent, but the effects of seasonality on pneumonia were more evident among the wealthiest.